NASCAR - Owens, Tom; Helmer, Diana Star 1962- (Brookfield, Conn. : Twenty-First Century Books, 2000)
Describes the fifty-year history of stock car racing, from its origins at Datona International Speedway in Florida in 1947 to current competitions among such drivers as Jeff Gordon, Dale Jarrett, and Dale Earnhardt.
Includes bibliographical references and index
ages 9-12
Keywords: NASCAR (Association) -- Juvenile literature; Stock car racing -- Juvenile literature. -- United States; Stock car racing